Beating the drum for war: The pro-imperialist tour of the pseudo left (World Socialist Web Site, 2023)
The tour's main purpose is to prop up the faltering US war propaganda of the “unprovoked” invasion of Ukraine by the Putin regime, and advocate for more weapons for Ukraine, i.e., extension of the bloodbath.
Keywords: soros; ukraine